ANALISIS KINERJA APARATUR PEMERINTAHAN SEKRETARIAT DAERAH KABUPATEN KAUR - Valensi, Valensi (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The aim of this research is to find out and understand the work of the Kaur Regency Regional Secretariat team. The research method used is quantitative descriptive with an inductive approach. The data used in this analysis are primary data and secondary data. Primary data will be processed based on the results of observations and interviews with Kaur Regency Regional Secretariat staff and other parties involved in the main functions and activities of the Kaur Regency Regional Secretariat. The data used in this analysis are primary data and secondary data. Primary data was processed through observation and interviews with Kaur Regency regional secretariat officials. Secondary data was obtained from Regional Secretary Kaur. The results of the analysis show that the performance of the Kaur Regency Regional Secretariat is good. This can be seen from indicators of productivity, service quality and responsiveness, responsibility and accountability. The results of the research show that leadership and cultural factors have a big influence on the achievements of the Kaur District secretariat team.